How ICT4D Research Fails the Poor - Harris, Roger W. (Taylor & Francis Group, 2016)
Research can improve development policies and practices and funders increasingly require evidence of such socioeconomic impact from their investments. This article questions whether information and communication technologies for development (ICT4D) research conforms to the requirements for achieving socioeconomic impact. We report on a literature review of the impact of research in international development and a survey of ICT4D researchers who assessed the extent to which they follow practices for achieving socioeconomic impact. The findings suggest that while ICT4D researchers are interested in influencing both practice and policy, they are less inclined toward the activities that would make this happen, especially engaging with users of their research and communicating their findings to a wider audience. Their institutions do not provide incentives for researchers to adopt these practices. ICT4D researchers and their institutions should engage more closely with the users of their research through more and better communications with the public, especially through the use of information and communication technologies.